ANALISIS PENGARUH PRESSURE DAN OPPORTUNITY UNTUK MENDETEKSI TERJADINYA KECURANGAN LAPORAN KEUANGAN - Friska, Yolanda; Sari, Maria Mediatrix Ratna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Financial statement analysis is the process to identify company’s information based on company’s condition. However, in recent years there have been accounting scandals or what is commonly referred to as financial statement fraud, which is a deliberate omission that results in material misstatements in financial statements. The purpose of this study was to determine the effect of pressure and opportunity to detect fraud in the financial statements. The sample of this study were 14 companies with purposive sampling technique from 47 mining companies listed on IDX 2017-2020. Secondary data in this study is accessed through www.idx.co.id and each company's website. The analytical technique used in this study uses multiple linear analysis. The results of the analysis show that ineffective monitoring has a positive effect on financial statement fraud, while external pressure and auditor opinion have no effect on financial statement fraud.